Texas Field Cricket, Gryllus texensis Cade and Otte (Insecta: Orthoptea: Gryllidae) - T.J. Walker (EDIS)
This document provides a detailed profile of the Texas field cricket, Gryllus texensis. It covers the cricket's distribution, identification, life cycle, habitat, and song. The article highlights the cricket's occurrence in western Florida, its unique trilling song, and its attraction to light. It also discusses the cricket's role in hybridization with other species and its economic impact. The document is part of the Featured Creatures collection, aimed at both laypersons with some biological knowledge and academic audiences. Published: January 1999.